G237(P) The Irish Junior Doctor Experience, Inclusive of EWTD Compliance. (24th May 2017) - Foley, D; Morrison, L; Neill, MO
Abstract : Aims: Recent implementation of the European Working Time Directive has been an important development in the training of Irish NCHDs, reducing long working hours and shift duration. Our aim was to identify strengths and deficiencies in current medical intern training including compliance to EWTD, education provided and also in identifying occupational difficulties faced by medical interns on a daily basis. Methods: Ethical approval was obtained for an online survey. A cross-sectional subjective analysis of 351 current interns was performed, following successful ethical approval. Both quantitative and qualitative analysis of results was carried out. Data was subsequently analysed and reviewed. Results: 158 (45%) of interns work shifts in excess of 24 hours, most noting clinical emergencies and team pressure as reasons for breach of EWTD. 39 (11%) of interns have worked shifts of duration greater than 28 hours, and 11 (3%) have worked a single shift in excess of 32 hours. Unrostered overtime was not financially compensated in 137 (39%) of interns. 75 (21.4%) interns have worked in excess of 90 hours per week on one or more occasions. Only 119 (34%) interns attend available training and education opportunities provided, more than 90% of the time. Conclusions: Irish hospitals are still poorly compliant with the European Working Time Directive despite industrial action, resulting in frustration and exhaustion results from unsafe working hours. These issues require to be addressed to improve the Irish intern experience.